COMPARATIVE STUDY OF PRE-TEST SCORE AND POST-TEST ON REGIONAL HEALTH PLANNING TRAINING - Supriyono Supriyono; Silviani Kesuma (Jurnal Ilmu Kesehatan, 2021)
Abstract. Background. This study aims to determine the differences in the results of teaching and learning training in regional health planning (Renkesda) in Batam National Health Training Center (Bapelkes) in 2016. Methods. The population in this study were all participants in the Renkesda training. The sample in this study was saturated, where all participants were taken as samples, with the number of respondents as many as 60 people. Before being subjected to treatment the two classes (X and Y) tested their homogeneity with different mean tests based on the average value of learning outcomes. Data collection methods are tests, observation, and documentation. Results and Discussion. The data analysis technique used was the Wilcoxon Signed Ranks Test which previously tested normality and homogeneity. The results of the study at the 95% significance level obtained p-value 0.556 and 0.908> 0.05. Thus it can be said that there were no differences in learning outcomes of class X and class Y. Furthermore when compared between pre and post-test, the following results were obtained: in class X Z value of -4,795 with a p-value of 0,000 <0,05 and in class Y Z value of -4,715 with the value of 0,000 <0,05. Conclusion. Based on Wilcoxon Signed Ranks Test test results, obtained Z value of -4,582 with a p-value of 0,000 <0.05, so it can be concluded that there are significant differences in the scores of the pre-test and post-test in class X and class Y Keywords: Renkesda, pre and post-test, comparative study